1998
DOI: 10.1023/a:1006848730927
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Chromatography of human myeloperoxidase (MPO) on a heparin-agarose column demonstrated a tight association of the protein with the resin. The electrophoretic mobility of mixtures of MPO and heparin in polyacrylamide gels under nondenaturing conditions was consistent with a strong interaction of the cationic enzyme with the polyanionic polysaccharide. Purified MPO prebound to bovine aorta endothelial cells (BAEC) and supplemented with hydrogen peroxide dose- and time-dependently abrogated the interaction of coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…In addition to HOCl cross-linking LDL via chloramines, which can subsequently react with lysine or histidine residues (66), a previously unsuspected oxidation pathway via cysteine-lysine interactions was also proposed, with likely relevance in the pathogenesis of atherosclerosis (68). Our evidence strongly supports this possibility, particularly as MPO (69) and S100A9 (Figs. 1D and 2E) bind glycosaminoglycans on EC and the ECM, and S100A8 preferentially forms non-covalent complexes with S100A9 (10), so the close proximity of these proteins may initially reduce oxidative damage.…”
Section: Figure 7 Separation Of Hocl-oxidized Proteinssupporting
confidence: 73%
“…In addition to HOCl cross-linking LDL via chloramines, which can subsequently react with lysine or histidine residues (66), a previously unsuspected oxidation pathway via cysteine-lysine interactions was also proposed, with likely relevance in the pathogenesis of atherosclerosis (68). Our evidence strongly supports this possibility, particularly as MPO (69) and S100A9 (Figs. 1D and 2E) bind glycosaminoglycans on EC and the ECM, and S100A8 preferentially forms non-covalent complexes with S100A9 (10), so the close proximity of these proteins may initially reduce oxidative damage.…”
Section: Figure 7 Separation Of Hocl-oxidized Proteinssupporting
confidence: 73%
“…(208) The nature of some of these caeruloplasmin-MPO complexes has been investigated. (209) Polyanionic glycosaminoglycans, such as the anticoagulant heparin, bind (cationic) MPO electrostatically, (28) and can liberate MPO sequestered in the artery wall. (210) This interaction with MPO may exacerbate damage to heparin, or other glycosaminoglycans to which it is bound, (84,155) but divert oxidation from other critical sites.…”
Section: Inhibition Of Myeloperoxidase Activitymentioning
confidence: 99%
“…The main reason for this is the fact that MPO rapidly adsorbs at the surface of LDL and seems to have a strong interaction with the protein moiety of LDL [93, 94]. This adsorption phenomenon is due to the cationic characteristic of MPO, and it has been described on lipoproteins and also on endothelial cells [95]. LDL-MPO bound was first shown by Carr et al who observed a coprecipitation of apoB-100-containing lipoproteins and MPO.…”
Section: Modification Of Ldl Myeloperoxidase and Mox-ldlmentioning
confidence: 99%